以多群組結構方程模式檢驗成就目標理論模式的測量恆等性 Verifying the Invariance of a Measurement Model for Achievement Goals Theory by Using the Multiple Group Structural Equation Modeling - 吳中勤 Chung-Chin Wu (National Taiwan Normal University, 2014)
成就目標測量存在著測量內容、理論再概念化以及理論模式類推適用等問題，尚未受到研究的重視及實徵的檢驗。本研究之主要目的在於：一、修正成就目標測量的問題，編製六向度成就目標量表，透過競爭模式選擇適配度最佳且最具簡效性之模式；二、針對理論模式進行跨群組恆等性的檢驗；三、探討性別與教育階段對六向度成就目標的影響。研究結果顯示：一、六向度成就目標測量具有良好的信度與建構效度，為適配度最佳且最具簡效性之理論模式；二、測量具良好的跨性別群組恆等性及適中的跨教育階段測量的恆等性；三、普遍而言，男生抱持了較高的趨向導向與逃避導向目標，顯示出成就目標的複雜性。根據本研究發現，於文末提出相應之建議。 The appropriateness of measure content, ambiguity of theoretical concepts, and interferences of theoretical measure are three problems in achievement goal research. These problems have yet to receive comprehensive attention or empirical examinations. The purposes of this study were (1) to revise the problems caused by achievement goal measures and to compile a Mandarin version of a 3×2 achievement goal measure (the best fit and most parsimonious model was chosen based on model comparisons), (2) to examine the multiple group invariance of the theoretical model by utilizing multiple group structural equation modeling, and (3) to investigate the influences of gender and the educational phase on each of the 3×2 achievement goals. The results are summarized as follows: (1) the measurement of 3×2 achievement goals yielded favorable reliability and construct validity. Moreover, this model is regarded as the best fit and the most parsimonious model. (2) The measurement presents favorable validity between gender and moderate validity between the educational phase. (3) In general, boys pursued higher approach- and avoidance-oriented goals than girls, indicating the complexity of achievement goals. Suggestions are proposed based on these findings presented at the end of the article.